COOPERATIVE TIPE JIGSAW DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN AQIDAH AKHLAK DI MI AL AZHAR SAMBONG DUKUH JOMBANG - hidayatur rohmah (JoEMS (Journal of Education and Management Studies), 2019)
The jigsaw type cooperative learning model is a learning model that focuses on student group work in the form of small groups. The purpose of the study was to determine the application of jigsaw type cooperative learning that affects student learning activeness and the obstacles faced in the study of moral aqeedah. This research is a classroom action research that lasts two cycles. Overall, the results of the study that lasted two cycles showed that learning using the cooperative model of the jigsaw type in Aqidah Akhlak learning could increase student learning activeness by 87.5%. Student response. the implementation of the cooperative model of the jigsaw type is very positive. The results of this study indicate that the application of the cooperative type jigsaw model can increase student learning activeness and get a very positive response from students with a value range of 3.50. So, the teacher can apply the cooperative model of the jigsaw type in the learning of Aqidah Akhlak.